Assessment of the quality of continuous evaluation in the LMD system from the viewpoint of teachers - a field study at the University of Akli Mhaned Oulhadj Bouira - Kouadri, Sarra (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
The current study focused on the quality of the continuous evaluation practiced under the LMD system, where it aimed to know the evaluations of professors of the quality of the continuous evaluation according to the LMD system. To achieve the objectives of the study, the descriptive approach was used based on the questionnaire of 28 words spread over five axes, it was distributed after confirming its sekumetric characteristics to a sample of 83 professors selected in a random manner on a regular basis from the various faculties of The University of Akli Mhaned Oulhadj In Bouira, and the study reached several results, the most important of which were : The quality of continuous evaluation practiced under the LMD system is generally average so that : - The level of quality of continuous evaluation according to the standards of comprehensiveness and continuity and objectivity and efficiency is average. - The quality of continuous evaluation according to the standards of ease and economy and taking into account individual differences is low. The results also showed that there are no statistically significant differences in the teachers' assessments of the quality of the continuous evaluation due to the changes of scientific degree and the years of experience, while there were statistically significant differences in the teachers' assessments of the quality of the continuous evaluation due to the academic specialization in favor of the literary, human and social disciplines.